Das Geschäft mit der Stadt : Zum Verhältnis von Ökonomie, Architektur und Stadtplanung - ÖGfA (UmBau, 2015)
The current issue of the journal UmBau examines the interconnections between the economy and urban planning and seeks alternatives to current planning imperatives. Are there private alternatives to public financing of public buildings and spaces? What are the implications of public responsibility for urban planning, and how is this responsibility fulfilled? These are interdisciplinary questions.